Environmental Education: Optimizing Household Waste Management in Singaparna, Gresik Through P-Graph Process Network Synthesis - Muh Farid; Restu Auliani; Nelson Tanjung; Erba Kalto Manik; Mustar Rusli (Departement of Mathematics Education, 2024)
Improper handling and disposal of waste can result in water and air pollution, which has the potential to cause disease. This problem is further exacerbated by the increase in the amount of waste which is not commensurate with waste management capacity. Therefore, this research aims to provide appropriate recommendations for handling waste in Sangkapura District. One of the proposed solutions is to process organic waste into alternative energy sources using selected technology. It is hoped that this approach can reduce the volume of waste and provide alternative fuel for industrial activities. The quality of the product produced is also influenced by the selection of production units, which in this research is determined using the P-graph and Process Network Synthesis (PNS) tools. The PNS optimization model simulation results show that the most optimal operational process scenario is scenario 2, which involves initial sorting or PS_12, Biodigester_2, Sorting, and RDF or PRDF Production.